2018
DOI: 10.1002/dmrr.3082
|View full text |Cite
|
Sign up to set email alerts
|

GLP‐1 receptor agonist added to insulin versus basal‐plus or basal‐bolus insulin therapy in type 2 diabetes: A systematic review and meta‐analysis

Abstract: Background Current guidelines recommend that antihyperglycaemic treatment in patients with type 2 diabetes not achieving the HbA1c target on basal insulin should be intensified with a glucagon‐like peptide‐1 receptor agonist (GLP‐1RA) or basal‐plus/basal‐bolus (BP/BB) insulin regimen. We conducted a systematic review and meta‐analysis to compare the effects of GLP‐1RA/insulin combinations versus BP/BB. Methods The review was registered on PROSPERO (CRD42017079547). PubMed, Scopus, CENTRAL, and http://ClinicalT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 34 publications
4
52
0
3
Order By: Relevance
“…Several studies have compared a basal‐bolus insulin regimen with a GLP1RA plus basal insulin regimen . These studies have consistently shown similar lowering of HbA1c, along with a beneficial impact on body weight and lower hypoglycaemia associated with the combined GLP1RA approach . However, none of these trials enrolled patients with HbA1c >10.5%, limiting the translatability of their findings for this more challenging patient population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Several studies have compared a basal‐bolus insulin regimen with a GLP1RA plus basal insulin regimen . These studies have consistently shown similar lowering of HbA1c, along with a beneficial impact on body weight and lower hypoglycaemia associated with the combined GLP1RA approach . However, none of these trials enrolled patients with HbA1c >10.5%, limiting the translatability of their findings for this more challenging patient population.…”
Section: Discussionsupporting
confidence: 91%
“…23,24,[28][29][30] These studies have consistently shown similar lowering of HbA1c, along with a beneficial impact on body weight and lower hypoglycaemia associated with the combined GLP1RA approach. 31 However, none of these trials enrolled patients with HbA1c >10.5%, limiting the translatability of their findings for this more challenging patient population. We report here the first randomized trial enrolling only patients with highly elevated HbA1c, who are significantly underrepresented in clinical trials, and thus provide much needed clinical evidence to guide treatment decisions for this very uncontrolled patient population.…”
Section: Discussionmentioning
confidence: 99%
“…BI and GLP‐1RAs potentiate each other by acting through different mechanisms in different tissues . Addition of GLP‐1RAs to a basal oral therapy is as effective as addition of bolus insulin with respect to glycaemic control, but with lower risk of hypoglycaemia and weight gain, and lower insulin doses . Therapeutic inertia in treating patients with uncontrolled T2D can worsen cardiovascular outcomes, and intensification of a basal oral regimen is often delayed in clinical practice while timely addition of a GLP‐1RA to BI could improve clinical and economic outcomes …”
Section: Introductionmentioning
confidence: 99%
“…7,8 Addition of GLP-1RAs to a basal oral therapy is as effective as addition of bolus insulin with respect to glycaemic control, but with lower risk of hypoglycaemia and weight gain, and lower insulin doses. 9 Therapeutic inertia in treating patients with uncontrolled T2D can worsen cardiovascular outcomes, 10 and intensification of a basal oral regimen is often delayed in clinical practice 11 13 However, many patients in clinical practice do not receive high doses of BI, implying that the GLP-1RA dose in the FRC may be under-titrated. Compared with FRCs, flexible combinations of BI and GLP-1RA are burdened by the higher numbers of injections and regimen complexity, but have the advantage of being able to combine any BI with any GLP-1RA, each at the desired dose.…”
Section: Introductionmentioning
confidence: 99%
“…25 Among the reported 13 studies, AWARD-4 and AWARD-7 26 were the only studies evaluating the combination of a GLP-1 RA with up-titrated prandial insulin. However, results from the AWARD-4 study are in line with results from the combination of GLP-1 RAs with insulin that was evaluated in a recent meta-analysis in comparison to a basal-bolus or basal-plus regimen (mean body weight difference, −3.72 kg).…”
Section: Discussionmentioning
confidence: 99%